Beyond nature vs. nurture in expertise research - comment on Baker & Wattie - David Z. Hambrick; Alexander P. Burgoyne (Bern Open Publishing, 2019)
The field of expertise is mired in a nature vs. nurture debate. Despite what we now know from behavioral genetics research about the underpinnings of human behavior, some expertise theorists continue to deny or downplay the importance of genetic factors ("innate talent") in expert performance. In this commentary, we argue that this viewpoint is neither defensible nor productive. Our argument is based on two observations. First, there are always limits on human performance, even among individuals who have engaged in long periods of intensive training. Second, grounded in a neurobiological system that has evolved through natural selection, variation across people in phenotypes reflecting these limits will have a genetic component. We comment on directions for future research to advance the field of expertise.